Effects of whole and steam-flaked corn supplementation on productive performance, serum parameters, and reproductive characteristics of dairy ewes - H. I. Akbağ; C. Tölü; T. Savaş; A. Konyalı; B. Coşkun; İ. Y. Yurtman; İ. Y. Yurtman (Archives Animal Breeding)
This study aimed to determine the effects of whole and steam-flaked corn supplementation on the feed intake, serum parameters, and reproductive performance of dairy ewes. A total of 48 ewes (at the end of their lactation period; 57 ± 1.3 kg body weight, BW; 2.69 ± 0.19 body condition score, BCS) were divided into three treatment groups (16 animals per group): the control group (C), which was fed with alfalfa hay and corn silage; the whole-corn group (WC), which was fed with alfalfa hay, corn silage, and whole corn; and the steam-flaked corn group (FC), which was fed with alfalfa hay, corn silage, and steam-flaked corn. The study was conducted for 15 d before ram introduction and for 30 d during the mating in the breeding season. The WC group had higher dry matter (DM), metabolizable energy (ME), and starch intake values than the FC group (P<0.0001). The BW and BCS values were increased in the groups supplemented with whole corn and steam-flaked corn (P≤0.05). The lambing rate was higher in ewes from the WC and FC groups (P≤0.05). Whole and steam-flaked corn supplementation did not affect the non-return ratio or litter size (P>0.05). The serum glucose concentration was similar among the groups, whereas the serum urea concentration increased with either whole or steam-flaked corn supplementation (P≤0.05). In conclusion, whole and steam-flaked corn supplementation increased the BW, BCS, and lambing rate values in dairy ewes.